The Existence of Noken in the Era of Modernization and Globalization: A Study of the Identity of Indigenous Papuans in Jayapura City - Nurwiati Nurwiati; Abinus Sama; Taufiq Al Islam Asrul; Nanita Tabuni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Noken is a cultural heritage of the Indigenous Papuan People (OAP) that holds strong social, cultural, and symbolic meaning. Amidst the currents of globalization and modernization in Jayapura City, the existence of noken faces challenges in the form of lifestyle changes, penetration of industrial products, and shifts in cultural values. This study aims to analyze how noken survives as an OAP identity in urban spaces, as well as the adaptation strategies undertaken by Papuans in maintaining the meaning and function of noken. The study used a qualitative approach with in-depth interviews, observations, and documentation studies. The results show that noken functions not only as a tool, but also as a symbol of identity, ethnic pride, and a medium for cultural negotiation amidst globalization. The sustainability of noken is supported by the role of Papuan women, cultural policies, and innovations in design and marketing.